2019
DOI: 10.1002/app.48896
|View full text |Cite
|
Sign up to set email alerts
|

Effect of incorporation of microstructured carbonized cellulose on surface and mechanical properties of epoxy composites

Abstract: In this study, we reported the use of cellulose derived microstructured biochars for the production of reinforced plastics. Cellulose nanocrystals and wasted cotton fibers were used as cellulose template structures and converted into carbonaceous materials under pyrolytic conditions. Biochars particles were produced with the shape of deformed spheres or rods and dispersed into an epoxy matrix with a loading ranging from 1 wt % to 10 wt %. Biochar-based composites showed remarkably elongation properties of up t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 46 publications
(43 reference statements)
1
13
0
Order By: Relevance
“…In a rough comparison with fibres loaded with 20 wt.% CNTs, biochar containing composites displayed far lower conductivity, and this was understandable because of the significant difference in the conductivities of the fillers themselves. In line with Noori et al [ 25 ], biochar produced at 1000 °C showed an electric behaviour close to that of metal, but it was still far from the conductive values of CNTs. Another advantage of the Biochar material is seen here, namely the possibility of its greater compaction in the composite.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…In a rough comparison with fibres loaded with 20 wt.% CNTs, biochar containing composites displayed far lower conductivity, and this was understandable because of the significant difference in the conductivities of the fillers themselves. In line with Noori et al [ 25 ], biochar produced at 1000 °C showed an electric behaviour close to that of metal, but it was still far from the conductive values of CNTs. Another advantage of the Biochar material is seen here, namely the possibility of its greater compaction in the composite.…”
Section: Resultssupporting
confidence: 87%
“…Derived from recycled cotton fibres, Biochar is synthesized as described [ 24 , 25 ]. To produce the composite in the form of fibres, the screw extruder (purpose-designed and assembled at the Faculty of Mechatronics, WUT) was used.…”
Section: Methodsmentioning
confidence: 99%
“…Table 1 further gives the values corresponding to the rate of max decomposition, onset of degradation, and residue percentage as shown in Figure 7. 44 The results from DMA graphs shown in Figure 8 illustrate storage modulus versus temperature of neat epoxy resin compared with biochar infused epoxy resin. The peak of the storage modulus curve is of interest to highlight the initial stiffness of the material at room temperature.…”
Section: Resultsmentioning
confidence: 99%
“…Authors concluded that porous nature of the biochar particles reduced the void content and enhanced the interfacial bonding. Mattia Bartoli et al 27 incorporated microstructured biochar materials from cellulose and waste cotton fibers into epoxy composites and studied mechanical behavior of developed composites. From experimental results it was noticed addition of 5% biochar materials to epoxy composites improved tensile strength by 57% and 10% biochar epoxy composites exhibited low friction coefficient i.e., 0.22.…”
Section: Introductionmentioning
confidence: 99%